Swimming behavior of tambakan fish (Helostoma temminckii) based on the varying current speed in a mini flume tank - Tiza Zaslin; Nofrizal Nofrizal; Riska Fatmawati; Romie Jhonnerie; Dhita Widhiastika (Jurnal Perikanan Terpadu, 2025)
Understanding the swimming behavior and patterns of tambakan fish (Helostoma temminckii) is crucial for advancing fishing technology. This study aimed to identify the effect of current on the swimming speed behavior of Helostoma temminckii within a mini flume tank. Experiments were conducted using different current speeds to observe three categories of swimming speed: sustained swimming speed, prolonged swimming speed, and burst swimming speed. Observations were performed using video recordings to analyze tail beat frequency and amplitude, as well as the correlation between these variables and the fish's swimming speed and endurance. The results revealed that current speeds had a significant influence on the swimming performance of Helostoma temminckii. The maximum sustained swimming speed ranged from 1.61 to 2.21 BL/s, while prolonged swimming occurred within 1.61–6.98 BL/s, with swimming durations between 15 seconds and less than 200 minutes. Burst swimming speed reached up to 6.20 body lengths per second (BL/s) and lasted under 15 seconds. Several factors were found to influence the swimming behavior of Helostoma temminckii, including a strong negative correlation between swimming speed and endurance (R² = 0.8259). Moreover, a positive correlation was observed between tail-beat frequency and swimming speed (R² = 0.8852) and between tail-beat amplitude and frequency (R² = 0.9454). These findings have significant implications for designing more efficient and selective fishing gear by taking into account fish physiology. The study provides a critical foundation for the development of environmentally friendly fishing technologies and a better understanding of the swimming behavior of native fish species.